Effect of employee’s satisfaction on performance of Nigerian microfinance banks - Abass Adekunle Adewale; Abass Adedolapo Adeyemo; Saidat Busayo Lawal (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Міжнародні відносини, економіка, країнознавство, туризм)
The study investigates the nexus between employee satisfaction and the performance of selected Microfinance banks in Nigeria, with a focus on five banks in Osun State. It aims to discern the relationship between employee satisfaction and bank performance, while pinpointing key factors that influence employee satisfaction, such as prompt salary, job security, and fringe benefits. Utilizing a purposive sampling technique, data from 40 employees were collected through structured questionnaires, and subsequent analysis involved descriptive statistics and regression. Results indicate a robust positive correlation between employee satisfaction and bank performance, with prompt salary payment, job security, and fringe benefits emerging as significant influencers of satisfaction. The study underscores the importance of proactive measures by microfinance banks to augment employee satisfaction, particularly in these critical areas. Strengthening employee engagement is posited as pivotal for sectoral performance enhancement. By prioritizing the well-being and contentment of their workforce, microfinance banks can cultivate a conducive work environment conducive to heightened efficiency and effectiveness.